(untitled) (Aethiopica, 2010)
The phonology belongs to the basic structures of a language. Knowing the sounds of the phonemes of a language is essential for the grammar, etymology or classification of a given language. For ancient languages (extinct or classical), phonology is always problematic, for obvious reasons. In this paper, various approaches are evaluated and combined that can shed light on how Gəʿəz might have sounded in Aksumite times: transcriptions in contemporary language, transcriptions and loanwords from contemporary languages, traditional pronunciation, the phonology of the daughter languages, and comparative evidence.